Occulomotor Neural Integrator Dysfunction in Multiple Sclerosis: Insights From Neuroimaging - Bede, Peter; Finegan, Eoin; Chipika, Rangariroyashe H.; Li Hi Shing, Stacey; Lambe, Jeffrey; Meaney, James; Redmond, Janice (Frontiers in Neurology, 2018)
Background: Magnetic resonance imaging is a key diagnostic and monitoring tool in multiple Sclerosis (MS). While the substrates of motor and neuropsychological symptoms of MS have been extensively investigated, nystagmus-associated imaging signatures are relatively under studied. Accordingly, the objective of this study is the comprehensive characterisation of cortical, subcortical and brainstem involvement in a cohort of MS patients with gaze-evoked nystagmus. Methods: Patients were recruited from a specialist MS clinic and underwent multimodal neuroimaging including high-resolution structural and diffusion tensor data acquisitions. Morphometric analyses were carried out to evaluate patterns of cortical, subcortical, brainstem and cerebellar grey matter pathology. Volumetric analyses were also performed to further characterise subcortical grey matter degeneration. White matter integrity was evaluated using axial-, mean-, and radial diffusivity as well as fractional anisotropy. Results: Whole-brain morphometry highlighted considerable brainstem and cerebellar grey matter atrophy, and the tract-wise evaluation of white matter metrics revealed widespread pathology in frontotemporal and parietal regions. Nystagmus-associated grey matter degeneration was identified in medial cerebellar, posterior medullar, central pontine and superior collicular regions. Volume reductions were identified in the putamen, thalamus and hippocampus. Conclusions: Multiple sclerosis is associated with widespread grey matter pathology which is not limited to cortical regions but involves striatal, thalamic, cerebellar and hippocampal foci. The imaging signature of gaze-evoked nystagmus in MS confirms the degeneration of key structures of the neural integrator network.